Assessing Bioenergetic Compromise in Autism Spectrum Disorder With 31P Magnetic Resonance Spectroscopy: Preliminary Report. (February 2014) - Golomb, Beatrice A.; Erickson, Laura C.; Zeeland, Ashley A. Scott-Van; Koperski, Sabrina; Haas, Richard H.; Wallace, Douglas C.; Naviaux, Robert K.; Lincoln, Alan J.; Reiner, Gail E.; Hamilton, Gavin
We sought to examine, via Phosphorus-31 magnetic resonance spectroscopy ( 31 P-MRS) in a case-control design, whether bioenergetic deficits in autism spectrum disorders extend to the brain and muscle. Six cases with autism spectrum disorder with suspected mitochondrial dysfunction (age 6-18 years) and 6 age/sex-matched controls underwent 31 P magnetic resonance spectroscopy. The outcomes of focus were muscle resting phosphocreatine and intracellular pH as well as postexercise phosphocreatine recovery time constant and frontal brain phosphocreatine. Intracellular muscle pH was lower in each autism spectrum disorder case than their matched control (6/6, P = .03; P = .0048, paired t test). Muscle phosphocreatine (5/6), brain phosphocreatine (3/4), and muscle phosphocreatine recovery time constant (3/3) trends were in the predicted direction (not all participants completed each). This study introduces 31 P magnetic resonance spectroscopy as a noninvasive tool for assessment of mitochondrial function in autism spectrum disorder enabling bioenergetic assessment in brain and provides preliminary evidence suggesting that bioenergetic defects in cases with autism spectrum disorder are present in muscle and may extend to brain.